Deciphering Iron-Catalyzed C−H Amination with Organic Azides: N2 Cleavage from a Stable Organoazide Complex - Stroek, Wowa; Keilwerth, Martin; Malaspina, Lorraine A.; Grabowsky, Simon; Meyer, Karsten; Albrecht, Martin (Chemistry - A European Journal, 2023)
Catalytic C−N bond formation by direct activation of C−H bonds offers wide synthetic potential. En route to C−H amination, complexes with organic azides are critical precursors towards the reactive nitrene intermediate. Despite their relevance, α-N coordinated organoazide complexes are scarce in general, and elusive with iron, although iron complexes are by far the most active catalysts for C−H amination with organoazides. Herein, we report the synthesis of a stable iron α-N coordinated organoazide complex from [Fe(N(SiMe3)2)2] and AdN3 (Ad=1-adamantyl) and its crystallographic, IR, NMR and zero-field 57Fe Mössbauer spectroscopic characterization. These analyses revealed that the organoazide is in fast equilibrium between the free and coordinated state (Keq=62). Photo-crystallography experiments showed gradual dissociation of N2, which imparted an Fe−N bond shortening and correspond to structural snapshots of the formation of an iron imido/nitrene complex. Reactivity of the organoazide complex in solution showed complete loss of N2, and subsequent formation of a C−H aminated product via nitrene insertion into a C−H bond of the N(SiMe3)2 ligand. Monitoring this reaction by 1H NMR spectroscopy indicates the transient formation of the imido/nitrene intermediate, which was supported by Mössbauer spectroscopy in frozen solution.
CRIS-Team Scopus Importer:2023-12-08
Keywords: C−H amination; nitrenes; organoazides; photocrystallography; reaction mechanisms